MRI/DTI atlas of the human brainstem in transverse and sagittal planes. (2023) - Paxinos, George, 1944-; Furlong, Teri; Ashwell, Ken; Smith, Kristie; Calabrese, Evan; Johnson, G. Allan
No abstract available